A new geometrical approach to solve inverse kinematics of hyper redundant robots with variable link length - Jamali, Annisa; Khan, Md. Raisuddin; Rahman, Md. Mozasser (2011)
In this paper a new approach that generates a general algorithm for n-link hyper-redundant robot is presented. This method uses repetitively the basic inverse kinematics solution of a 2- link robot on some virtual links,where the virtual links are defined following some geometric proposition. Thus, it eliminates the mathematical complexity in computing inverse kinematics solution of n-link hyper redundant robot. Further, this approach can handle planar manipulator with variable links eliminating singularity. Numerical simulations for planar hyper redundant models are presented in order to illustrate the competency of the model.